Alleles and haplotypes of bone marrow donors recruited in the Оrenburg region - D. N. Smirnova; M. A. Loginova; O. A. Makhova; I. P. Obukhov; J. I. Dudina; N. A. Morozova; I. V. Paramonov (Сибирский научный медицинский журнал, 2025)
Aim of the study was to investigate the frequency of occurrence of HLA alleles and five-locus haplotypes in hematopoietic stem cell donors - residents of the Orenburg region.   Material and methods. HLA typing of 5529 potential donors of the Orenburg region of the Russian Federation using NGS technology in 2-field resolution at the HLA-A, HLA-B, HLA-C, HLA-DRB1 and HLA-DQB1 loci was performed.   Results and discussion. 74 alleles were identified at the HLA-A locus, 108 at the HLA-B locus, 68 at the HLA-C locus, 65 at the HLA-DRB1 locus, and 37 at the HLA-DQB1 locus. The most common alleles are HLA-A*02:01 (25.85 %), HLA-A*03:01 (12.96 %), HLA-A*01:01 (11.66 %), HLA-B*07:02 (10.70 %), HLA-B*18:01 (7.40 %), HLA-B*08:01 (6.39 %), HLA-C*04:01 (13.22 %), HLA-C*07:02 (12.43 %), HLA-C*07:01 (11.70 %), HLA-DRB1*07:01 (13.75 %), HLA-DRB1*15:01 (10.93 %), HLA-DRB1*01:01 (10.55 %), HLA-DQB1*03:01 (21.23 %), HLA-DQB1*05:01 (13.23 %), HLA-DQB1*02:02 (11.02 %). Among five-locus haplotype in the studied population the most common is HLA-A*01:01~HLA-C*07:01~HLA-B*08:01~HLA-DRB1*03:01~HLA-DQB1*02:01 (3.66 %). 26 new alleles have been described.   Conclusions. The examined population of donors recruited in the Orenburg region, according to the distribution of the most common alleles and haplotypes, has great similarity with the studied populations of the European part of Russia, however, a large number of identified rare and new alleles indicates the relevance of further research and recruitment of donors in this region in order to increase the genetic diversity of the Federal Register, which will increase the likelihood of matching a donor for any patient in need of hematopoietic stem cell transplantation.